Diseases of the sinuses : a comprehensive textbook of diagnosis and treatment - Gershwin, M. Eric; Incaudo, Garry A (Humana Press, 1996)
University of California, Davis. Interdisciplinary reference on the anatomy, physiology, imaging, diseases, and surgical management of the nasal and paranasal sinus. For immunologists, allergists, otolaryngologists.
Keywords: dospělí; otorinolaryngologie; Paranasal Sinuses; paranazální dutiny; Child; Infant; dítě; Sinusitis; kojenec; sinusitida; Adult